Cúbicas galoisianas - Rodrigues, Tatiana Miguel [UNESP] (Universidade Estadual Paulista (Unesp), 2003)
O propósito deste trabalho é abordar as cúbicas galoisianas as quais, pelo Teorema de Kronecker-Weber, estão contidas em uma extensão ciclotômica Q(dn), para algum n. Estudamos a representação geométrica do seu anel dos inteiros algébricos, que são reticulados de posto 3. Visando calcular a densidade de centro de tais reticulados, é necessário o estudo do discriminante dessas cúbicas e a minimização da função traço.

The purpose of this work is to deal with the galoisian cubics which, by Kronecker-Weber Theorem, are contained in a cyclotomic extension Q(dn); for some n. We study the geometric representation of their algebraic integer ring, which are lattices with rank 3. For calculating the center density of these lattices, it is necessary to study the discriminant of those cubics and the minimization of trace form.
Keywords: Álgebra; Teoria dos numeros algebricos; Teoria dos reticulados; Densidade de centro; Galoisian cubic; Lattices; Center density